Ethnic self-regulation and democratic instability on Nicaragua’s Atlantic Coast: The case of Ratisuna - Henriksen, Ken (European Review of Latin American and Caribbean Studies, 2008)
This article examines some of the negative impacts of ethnic self-regulation on the processes of democratization in Nicaragua. Based on a case study of a small Miskitu community on the Atlantic Coast the article argues that self-regulatory practices do not automatically forge the integration of civil society. On the contrary, these practices lead to an exclusionary development process that reinforces existing divisions and deepens ongoing conflicts. This argument is based on a distinction between three different, yet interrelated, expressions of neo-liberal change on the Atlantic Coast of Nicaragua: First, in the absence of state institutions the political influence of the ethnic minorities lies not in the ability to mobilize against the state, but in the fact that they fill the vacuum created by a state in retreat. Community members thus execute political authority and create social and political space. Second, the execution of political authority may contribute to the formation of community and the creation of space and social rights. But in this process other vulnerable groups are excluded, marginalized and denied access to basic rights. Thirdly, self-help practices lead to an exaggerated fragmentation of society into secluded and autonomous spatial and social units based on inward-looking principles.Resumen: Auto-regulación étnica e inestabilidad democrática en la costa atlántica de Nicaragua: El caso de RatisumaEn este artículo se estudian algunos de los efectos negativos de la auto-regulación étnica sobre los procesos de democratización en Nicaragua. Basándome en un caso de estudio de una pequeña comunidad miskito en la costa atlántica, en el artículo sostengo que las prácticas autoregulatorias no forjan automáticamente la integración de la sociedad civil. Al contrario, estas prácticas conducen a un proceso de desarrollo excluyente que refuerza las divisiones existentes y acentúa los conflictos en curso. Esta interpretación se basa en la distinción entre tres expresiones diferentes, aunque interrelacionadas, del cambio neo-liberal en la costa atlántica de Nicaragua: Primero, en la ausencia de instituciones estatales, la influencia política de las minorías étnicas no reposa en la capacidad de movilización contra el estado, sino en el hecho de que estas minorías llenan el vacío dejado por un estado en retirada. De este modo los miembros de la comunidad ejercen autoridad política y crean espacios sociales y políticos. Segundo, el ejercicio de autoridad política puede contribuir a la formación de la comunidad y a la creación de espacio y derechos sociales. Pero en este proceso se excluye a otros grupos vulnerables, marginándolos y negándoles el acceso a derechos básicos. Tercero, las prácticas de auto-ayuda conducen a una exagerada fragmentación de la sociedad en unidades espaciales y sociales recluidas y autónomas, centradas en sí mismas.